Field spectroscopy for the detection of underground military structures - Melillos, George; Agapiou, Athos; Themistocleous, Kyriacos; Michaelides, Silas; Papadavid, George; Hadjimitsis, Diofantos G. (My University, 2019)
Remote sensing is considered as an increasingly important technology for military intelligence. New satellite missions, such as Sentinel 2A, may provide systematic datasets for monitoring vast areas of interest. However, there is a great need to understand the information retrieved from such sensors. This paper contemplates the results obtained from a one-year field spectroradiometer campaign, aiming at the detection of underground military structures in Cyprus, covered with crops. The measurements were taken at the following test areas: (a) vegetation area covered with vegetation (barley), in the presence of an underground military structure, and (b) vegetation area covered with vegetation (barley), in the absence of an underground military structure. The ground hyperspectral signatures were resampled to the Sentinel-2A sensor using the appropriate Relative Spectral Response Filters (RSRF). Ten vegetation indices were utilized for the identification of the detection of underground military structures. Results have shown that differences exist between these ten vegetation indices, thus some of them are sufficient to distinguish the two areas. The phenological analysis of these measurements have shown the period of head emergence stage is suitable for monitoring crop marks. Sentinel-2A results were also validated with field spectroradiometer results which were acquired during a simultaneous in-situ campaign.
Keywords: Remote sensing; Spectroscopy; Military underground structures; Vegetation indices